Synthesis and transformation in the series of 2-((5-(2,4- and 3,4-dimethoxyphenyl)-3H-1,2,4-triazole-3-yl)thio)acetic acids - Dovbnia, D. V.; Kaplaushenko, A. H.; Frolova, Yu. S.; Довбня, Дмитро Віталійович; Каплаушенко, Андрій Григорович; Фролова, Юлія Сергіївна; Довбня, Д. В.; Каплаушенко, А. Г.; Фролова, Ю. С. (Запорізький державний медичний університет, 2021)
The aim of the work is to develop preparative methods for the synthesis of 2-((5-(2,4- and 3,4-dimethoxyphenyl)-3H-1,2,4-triazole-3-yl) thio)acetic acids, to study the esterification reaction in this regard, to study physical and chemical properties of the obtained substances, and to predict their toxicity. Materials and methods. Compounds were synthesized using reagents and solvents qualified as “ch.p.”. The IUPAC nomenclature as supplemented was used during the preparation. The melting temperature was determined with the capillary method according to HFC (2.2.14) on the device PTP (M). Elemental analysis was determined with the ELEMENTAR vario EL cube analyzer (manufactured in Germany) (standard – sulfonamide). IR spectra were recorded using spectrophotometer Specord M-80 (manufactured in Germany) within the range of 4000–500 cm-1 (scanning was performed under the following conditions: slot program 3.0, time constant – τ = 3 s, scanning time 34 min, samples were analyzed in the form of tablets with potassium bromide). 1H NMR spectra were recorded using Varian VXR-300 spectrophotometer (manufactured in the USA), dimethyl sulfoxide-D6 solvent, and tetramethylsilane was used as an internal standard. The spectra were decoded using the computer program ADVASP 1.43. Thin layer chromatography was performed using Sorbfil plates (analytical, size 10 × 15 cm, base: polymer substrate, sorbent: silica gel STX-1A, grain: 5–17 μm, layer thickness: 110 m combination – silicazole). Results. The synthesis of new 2-((5-(2,4- and 3,4-dimethoxyphenyl)-3H-1,2,4-triazole-3-yl)thio)acetic acids was carried out. These products became a basis for synthesis of a number of relevant esters. Physical and chemical properties were investigated for the synthesized compounds. The structure of the obtained substances was confirmed by elemental analysis, IR-spectroscopy, 1H NMR-spectrometry, and their individuality were established by thin-layer chromatography. Computer GUSAR-online prediction of acute toxicity of 2-((5-(2,4- and 3,4-dimethoxyphenyl)-3H-1,2,4-triazole-3-yl)thio)acetic acids and their esters was performed. Conclusions. Preparative methods for the synthesis of 2-((5-(2,4- and 3,4-dimethoxyphenyl)-3H-1,2,4-triazole-3-yl)thio)acetic acids have been developed, for which esterification reactions have been studied. Thus, physical and chemical properties of the received substances were investigated, and indicators of their toxicity were predicted. Мета роботи – розробити препаративні методики синтезу 2-((5-(2,4- та 3,4-диметоксифеніл)-3Н-1,2,4-тріазол-3-іл)тіо)ацетатних кислот, для яких вивчити реакцію естерифікації, дослідити фізико-хімічні властивості речовин, що отримали, та спрогнозувати параметри їхньої токсичності. Матеріали та методи. Синтез сполук виконали з використанням реактивів і розчинників, що мають кваліфікацію «х.ч.». Під час підготовчої роботи використали номенклатуру IUPAC із доповненнями. Температуру плавлення визначали капілярним способом за ДФУ (2.2.14) на приладі ПТП (М). Елементний аналіз виконали на аналізаторі ELEMENTAR vario EL cube (ФРН) (стандарт – сульфаніламід). ІЧ-спектри записували, використовуючи спектрофотометр Specord M-80 (ФРН) в області 4000–500 см-1 (сканування здійснювали в таких умовах: щільова програма 3.0, постійна часу – τ = 3 с, час сканування – 34 хв, проби аналізували у вигляді таблеток із калій бромідом). 1H ЯМР-спектри реєстрували з використанням спектрофотометра Varian VXR-300 (США), розчинник – диметилсульфоксид-D6, як внутрішній стандарт використали тетраметилсилан. Спектри розшифрували за допомогою комп’ютерної програми ADVASP 1.43. Тонкошарову хроматографію виконали, використовуючи пластинки Sorbfil (аналітичні, розмір 10 × 15 см, основа – полімерна підкладка, сорбент – силікагель СТХ-1А, зерно – 5–17 мкм, товщина шару – 110 мкм, речовина для сполучення – силіказоль). Результати. Здійснили синтез нових 2-((5-(2,4- та 3,4-диметоксифеніл)-3Н-1,2,4-тріазол-3-іл)тіо)ацетатних кислот, що стали основою отримання ряду відповідних естерів. Дослідили фізико-хімічні властивості синтезованих сполук. Будову речовин підтверджено за допомогою елементного аналізу, ІЧ-спектроскопії та 1Н ЯМР-спектрометрії, а їхня індивідуальність встановлена методом тонкошарової хроматографії. Виконали комп’ютерне GUSAR-online прогнозування гострої токсичності 2-((5-(2,4- та 3,4-диметоксифеніл)-3Н-1,2,4-тріазол-3-іл)тіо)ацетатних кислот та їхніх естерів. Висновки. Розробили препаративні методики синтезу 2-((5-(2,4- та 3,4-диметоксифеніл)-3Н-1,2,4-тріазол-3-іл)тіо)ацетатних кислот, для яких вивчили реакції естерифікації. Дослідили фізико-хімічні властивості речовин, що одержали, здійснили прогнозування показників їхньої токсичності. Цель работы – разработать препаративные методики синтеза 2-((5-(2,4 и 3,4-диметоксифенил)-3Н-1,2,4-триазол-3-ил)тио) ацетатных кислот, для которых изучить реакцию эстерефикации, исследовать физико-химические свойства полученных веществ, спрогнозировать параметры их токсичности. Материалы и методы. Синтез соединений проведен с использованием реактивов и растворителей, имеющих квалификацию «х.ч.». При подготовке работы использовали номенклатуру IUPAC с дополнениями. Температуру плавления определяли капиллярным способом по ГФУ (2.2.14) на приборе ПТП (М). Элементный анализ проведен на анализаторе ELEMENTAR vario EL cube (ФРГ) (стандарт – сульфаниламид). ИК-спектры записывали с использованием спектрофотометра Specord M-80 (ФРГ) в области 4000–500 см-1 (сканирование осуществляли в таких условиях: щелевая программа 3.0, постоянная времени – τ = 3 с, время сканирования – 34 мин, пробы анализировали в виде таблеток с калий бромидом). 1H ЯМР-спектры регистрировали с использованием спектрофотометра Varian VXR-300 (США), растворитель – диметилсульфоксид-D6, в качестве внутреннего стандарта использован тетраметилсилан. Спектры расшифровали с помощью компьютерной программы ADVASP 1.43. Тонкослойная хроматография проведена с применением пластинок Sorbfil (аналитические, размер 10 × 15 см, основа – полимерная подложка, сорбент – силикагель СТХ-1А, зерно – 5–17 мкм, толщина слоя – 110 мкм, вещество для связывания – силиказоль). Результаты. Проведен синтез новых 2-((5-(2,4 и 3,4-диметоксифенил)-3Н-1,2,4-триазол-3-ил)тио)ацетатных кислот, ставших основой получения ряда соответствующих эфиров. Изучили физико-химические свойства синтезированных соединений. Строение веществ подтверждено с помощью элементного анализа, ИК-спектроскопии и 1Н ЯМР-спектрометрии, а их индивидуальность установлена методом тонкослойной хроматографии. Проведено компьютерное GUSAR-online прогнозирование острой токсичности 2-((5-(2,4 и 3,4-диметоксифенил)-3Н-1,2,4-триазол-3-ил)тио)ацетатных кислот и их эфиров. Выводы. Разработаны препаративные методики синтеза 2-((5-(2,4 и 3,4-диметоксифенил)-3Н-1,2,4-триазол-3-ил)тио)ацетатных кислот, для которых изучены реакции эстерификации. Исследованы физико-химические свойства полученных веществ, проведено прогнозирование показателей их токсичности.
Синтез і перетворення в ряду 2-((5-(2,4- та 3,4-диметоксифеніл)-3Н-1,2,4-тріазол-3-іл)тіо)ацетатних кислот
Синтез и превращения в ряду 2-((5-(2,4- и 3,4-диметоксифенил)-3Н-1,2,4-триазол-3-ил)тио)ацетатных кислот
Довбня Д. В. - ORCID ID: 0000-0001-6170-144X; Каплаушенко А. Г. - ORCID ID: 0000-0003-3704-5539; Фролова Ю. С. - ORCID ID: 0000-0002-3995-5088.
Keywords: 2-((5-(2,4- and 3,4-dimethoxyphenyl)-3H-1,2,4-triazole-3-yl)thio)acetic acids; esters; toxicity indicators; 2-((5-(2,4- та 3,4-диметоксифеніл)-3Н-1,2,4-тріазол-3-іл)тіо)ацетатні кислоти; естери; показники токсичності; 2-((5-(2,4 и 3,4-диметоксифенил)-3Н-1,2,4-триазол-3-ил)тио)ацетатные кислоты; сложные эфиры; показатели токсичности